The effects of sesame oil and different doses of estradiol on testicular structure, sperm parameters, and chromatin integrity in old mice - Mohammadzadeh, Masoomeh (Clin Exp Reprod Med, 2021)
OBJECTIVE: Studies of the effects of estrogens on the male reproductive system have emphasized the role of these hormones in male fertility. Sesame oil has many phytoestrogenic compounds and may improve male fertility. This study investigated the effects of sesame oil and different concentrations of estrogen on sperm parameters and DNA integrity in male mice. METHODS: Twenty old NMRI (The Naval Medical Research Institute) male mice (40 weeks; weight, 30–35 g) were treated with sesame oil or different concentrations of estrogen (estradiol, 1 and 10 μL/kg/day) or received no treatment (controls). After 35 days, sperm parameters and DNA integrity were assessed and analyzed. RESULTS: Sperm count, progressive motility, and morphology were decreased in the group that received 10 μL/kg of estradiol. A remarkably lower percentage of DNA fragmentation and protamine deficiency were detected in the group that received 1 μL/kg of estradiol. In the groups that received sesame oil and 1 μL/kg of estradiol, the numbers of spermatogonia and Leydig cells were higher than in controls. The combination of sesame oil and 1 μL/kg of estradiol led to improved sperm parameters and chromatin and testicular structure. CONCLUSION: Based on this study, consumption of sesame oil and a low concentration of estradiol may improve testicular function in older mice.